Neuropharmacological profile of new thiazepinone and thiazolidinone compounds designed by virtual screening - Juan Sebastian Carrero-Sandoval; Paola Andrea Cuervo-Prado; Fabian Orozco-Lopez; Christian Alonso Becerra-Rivas; Estefany Arias-Quiroz; Mario Francisco Guerrero-Pabón (Brazilian Journal of Pharmaceutical Sciences)
Abstract To evaluate the neuropharmacological profile of new spiro thiazepinone and thiazolidinone compounds in CD1 mice after a computer-aided virtual screening based on a GABA-A/BZD site. From a library of 240 pyrazolo[1,4]thiazepin-3-ones and 39 pyrimidinyl thiazolidin-4-ones, two molecular prototypes of each series were selected by virtual screening using the rank consensus molecular docking approach, based on the GABA-A/BZD site. These compounds, coded as cpTP-0, cpTP-1, TAP-2 and cpTAP-2, were synthesised by multicomponent reactions and evaluated by neuropharmacological screening in CD1 mice (100 mg/kg, p.o.). The study revealed that cpTAP-2 exhibited a significant reduction of immobility time during the forced swimming test (FST), while it did not show any major effects in the rota-rod, open field, plus maze, tail suspension, pentylenetetrazole seizures, and barbiturate sleeping time tests. In a dose-response evaluation, cpTAP-2 reduced immobility time during forced swimming test in CD1 male mice at doses of 100 and 300 mg/kg with biologically relevant effect sizes. These results suggest that cpTAP-2 could elicit antidepressant effects possibly related to GABA-A/benzodiazepine site, although other mechanisms could be implicated.